Immanence and the vertigo of philosophy : from Kant to Deleuze - Kerslake, Christian (Plateaus., 2009)
One of the terminological constants in the philosophical work of Gilles Deleuze is the word 'immanence', and it has therefore become a foothold for those wishing to understand exactly what 'Deleuzian philosophy' is. Deleuze's philosophy of immanence is held to be fundamentally characterised by its opposition to all philosophies of 'transcendence'. On that basis, it is widely believed that Deleuze's project is premised on a return to a materialist metaphysics. Christian Kerslake argues that such an interpretation is fundamentally misconceived, and has led to misunderstandings of Deleuze's philosophy, which is rather one of the latest heirs to the post-Kantian tradition of thought about immanence. This will be the first book to assess Deleuze's relationship to Kantian epistemology and post-Kantian philosophy, and will attempt to make Deleuze's philosophy intelligible to students working within that tradition. But it also attempts to reconstruct our image of the post-Kantian tradition, isolating a lineage that takes shape in the work of Schelling and Wronski, and which is developed in the twentieth century by Bergson, Warrain and Deleuze.